2013
DOI: 10.1055/s-0032-1326284
|View full text |Cite
|
Sign up to set email alerts
|

Improving hand hygiene adherence in an endoscopy unit

Abstract: Hand hygiene rates were low before the education intervention and improved significantly after it. Against expectations, adherence to hand hygiene practices had increased further at 10 months after the intervention, reinforcing the intervention's positive impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Recently, it was reported that the most common infection route was the hands of healthcare staff, so the hand hygiene of doctors and nurses is now an important issue 4. However, a variety of electronic devices are installed in almost every corner of a hospital, such as the outpatient ward and examination rooms, owing to the computerization of a hospital system and the development of test equipment, e.g., artificial respirators in the intensive care units, computer-aided prescription systems for doctors and nurses, endoscopes, and ultrasonography systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the most common infection route was the hands of healthcare staff, so the hand hygiene of doctors and nurses is now an important issue 4. However, a variety of electronic devices are installed in almost every corner of a hospital, such as the outpatient ward and examination rooms, owing to the computerization of a hospital system and the development of test equipment, e.g., artificial respirators in the intensive care units, computer-aided prescription systems for doctors and nurses, endoscopes, and ultrasonography systems.…”
Section: Discussionmentioning
confidence: 99%
“…Given the characteristics of a gastrointestinal endoscopy room, pathogens can spread more often through the hands of healthcare staff who are easily exposed to body fluids of patients than through any other infection routes. Hence, it is thought that a variety of pathogens are likely to exist on the surface of the equipment inside the endoscopy room 4. However, to the best of our knowledge, no study has been conducted on the presence of pathogens in the endoscopy room so far.…”
Section: Introductionmentioning
confidence: 99%
“…Data show the positive effect of training on patient safety [39,40,41] Pittet et al [40] showed that hospital-wide hygiene campaigns with training led to a reduction in hospital infections (from 16.9% to 9.9% in 4 years; p = 0.04), and reduced methicillin-resistant Staphylococcus aureus (MRSA) infections from 2.16 to 0.93 cases per 10,000 patient days (p < 0.001) [37]. Santos et al [41] evaluated hand hygiene compliance in endoscopy.…”
Section: Ensuring Reprocessing Quality and Infection Preventionmentioning
confidence: 99%
“…Santos et al [41] evaluated hand hygiene compliance in endoscopy. Due compliance with hand hygiene was initially 21.4% in total (medical staff 15%, nursing staff 30.5%).…”
Section: Ensuring Reprocessing Quality and Infection Preventionmentioning
confidence: 99%
“…Bei unseren Begehungen endoskopischer Abteilungen von Kliniken und endoskopierender Praxen standen die Einhaltung der Anforderungen der Hygiene an die Aufbereitung flexibler Endoskope und endoskopischen Zusatzinstrumentariums im Fokus der Überprüfungen. Händehygiene in der Endoskopie ist ein weiterer wichtiger Aspekt[24].Zwar stammen die meisten Berichte über im Zusammenhang mit endoskopischen Untersuchungen aufgetretene Infektionen aus den Jahren vor 2000 [1] und vor Veröffentlichung der KRIN-KO-Empfehlungen zur Endoskopaufbereitung 2002 [6] was jedoch nicht zu falscher Sicherheit über zwischenzeitlich erreichte Fortschritte führen darf. Das Risiko möglicher Übertragungen von Infektionserregern durch flexible Endoskope ist nach wie vor gegeben.…”
unclassified